Effectiveness of Monovalent Rotavirus Vaccine in Mozambique, a Country with a High Burden of Chronic Malnutrition - Chissaque, Assucênio (2022)
Funding Information: Funding: This research was funded by GAVI through the Centers for Disease Control and Prevention (CDC), Atlanta and World Health Organization, Regional Office for Africa (WHO/AFRO). African Research in Neglected Tropical Diseases (EFINTD, grant number 89539); Deutsche Forschungsge-meinschaft (DFG; grant number JO369/5-1); Fundo Nacional de Investigação (FNI); United States Agency for International Development (USAID; grant number AID-656-F-16-00002); the Calouste Gulbenkian Foundation from where A.C., F.M., and J.S. have a PhD fellowship. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.